The anticarcinogenic activity of plants compounds - Sugiyanto .; B. Sudarto; Edy Meiyanto; Agung Endro Nugroho; Umar A. Jenie (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The study was conducted to observe the effect of extracts of ngokilo (Gynura procumbens), beluntas (Pluchea indica), murbei (Morus alba) dan tapak doro (Vinca alba) leaves. Showed anticarcinogenic activity on lung tumor growth of mice. In the nex step, compounds having anticarcinogenic effect was isolated and identified, and evaluated on the cultures of meilomaand Vero cells. The results showed that non-polar fraction of ethanol extract of ngokilo leaves did not have anticarcinogenic activity, whereas the polar fraction show anticarcinogenic activity. At least there were three flavonoids (flavon or flavonol groups) in this polar fraction. It was only two of these flavonoids inhibit the growth of myeloma and Vero cells.Key words : ngokilo, Gynura procumbens, anticarcinogenic, flavonoid.